Fatigue crack growth analysis of surge line under thermal stratification conditions. (September 2019) - Tang, P; Luo, J C; Sun, L; Li, P Z
Abstract: As the connection between the pressurizer and the main pipeline of nuclear reactor, thermal stratification occurs in the pressurizer surge line during the operation. The thermal stratification through the pipe wall increases the possibility of plastic deformation and fatigue failure in the nozzle, tee, elbow and weld. So it is of great significance to carry out research on the fracture mechanics of surge line under thermal stratification conditions. Therefore, in this paper, based on the results of finite element analysis and ASME specifications, and with the results of pipeline stress analysis under temperature and pressure transient loads, the fatigue crack growth analysis of the surge line under thermal stratification conditions is carried out, and the technical means of suppressing crack propagation is explored, which provides a reference for the safe operation of the surge line of the nuclear power plant.